2011
DOI: 10.1007/s11010-011-1174-x
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetite induces oxidative stress and apoptosis in lung epithelial cells

Abstract: There is an ongoing concern regarding the biocompatibility of nanoparticles with sizes less than 100 nm as compared to larger particles of the same nominal substance. In this study, we investigated the toxic properties of magnetite stabilized with polyacrylate sodium. The magnetite was characterized by X-ray powder diffraction analysis, and the mean particle diameter was calculated using the Scherrer formula and was found to be 9.3 nm. In this study, we treated lung epithelial cells with different concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Abundant in all cell compartments, it constitutes the first line of the cellular defense mechanism against oxidative injury [16]. Previous studies demonstrated that ROS generation following GSH depletion caused mitochondrial damage and up-regulation of pro-apoptosis mediators [2,7,18]. We found MgNPs also significantly reduced the GSH level.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Abundant in all cell compartments, it constitutes the first line of the cellular defense mechanism against oxidative injury [16]. Previous studies demonstrated that ROS generation following GSH depletion caused mitochondrial damage and up-regulation of pro-apoptosis mediators [2,7,18]. We found MgNPs also significantly reduced the GSH level.…”
Section: Resultssupporting
confidence: 52%
“…Among MgNPs, Fe 3 O 4 -containing MgNPs (MgNP-Fe 3 O 4 ; magnetite) are the only MgNPs approved for clinical use. Magnetite has a cubic inverse spinel structure with oxygen forming a face-centered cubic (FCC) closed packing; the interstitial tetrahedral and octahedral sites are occupied by Fe cations [2]. Due to their unique physical, chemical, and mechanical features, MgNPs-Fe 3 O 4 have been used as magnetic resonance imaging contrast agents, targeted drug delivery systems, and hyperthermic agents when placed in an external magnetic field [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In detail, 24 hours after Saos-2 cells were plated, 4 different concentrations of FeHA and HA nanoparticles, in a range from 200 μg/ml up to 2000 μg/ml, were added to the culture medium. It should be noted that the concentrations used in this study were significantly higher than the normal concentration used in several nanoparticles studies, in fact even the lowest concentration (200 μg/ml) is in many cases nearly the highest concentration adopted by several groups [21,27,28]. In this regard, the aim of this study was to verify any toxic effects induced by the FeHA MNPs compared to the HA nanoparticles, keeping in mind future in vivo applications, where high nanoparticle accumulation in the cells could influence cell behaviour.…”
Section: Resultsmentioning
confidence: 88%
“…Foreign particles, infectious agents and chemicals can induce an inflammatory response in the lung leading to oxidative stress. Also with regard to magnetite, exposure to it has been shown to induce oxidative stress and deplete antioxidant levels in the lung epithelial cells, stimulating the apoptotic pathway for cell death 14 . Furthermore, magnetite particles have been revealed to induce concentration-dependent DNA damage and enhance reactive oxygen species production 6 and micronuclei induction 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Iron is a transition metal that is considered to play a pivotal role in modulating oxidative stress and other biological responses 13 , 14 , which are speculated to be the critical mechanisms in eliciting the adverse effects of iron particulate matter exposure. The Organization for Economic Cooperation and Development (OECD) has generated a list of 14 commercially important nanoparticulate materials, in order to explore the possible health effects and regulate occupational and nonoccupational exposure scenarios, and iron oxide is included in the list 15 .…”
Section: Introductionmentioning
confidence: 99%